Preparation method of composite fiber containing Tai Chi stone and fabric of composite fiber
By ultraviolet graft modification of polyethylene terephthalate and blending with Tai Chi stone micro powder, composite fibers containing Tai Chi stone were prepared, which solved the antibacterial and hydrophilic hygroscopic properties of polyester fibers and fabrics. The poor problem achieves higher antibacterial and hygroscopic rates.
Patent Information
- Application Number
- CN202411568769.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-05
AI Technical Summary
Polyester fibers and fabrics have poor antibacterial properties and hydrophilic and hygroscopic properties.
By ultraviolet graft modification of polyethylene terephthalate, the introduction of quaternary ammonium antibacterial groups and hydrophilic carboxylic groups, and melt blended with Taichi stone powder to granulate and spin, the preparation Compound fibers containing Tai Chi stone.
It significantly improves the antibacterial properties and hydrophilicity of the fiber, improves the moisture absorption rate of the fabric, and has better health care effects.
Smart Images

Figure BDA0005119917750000031 
Figure BDA0005119917750000071 
Figure BDA0005119917750000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of fiber technology, and in particular to a preparation method of composite fiber containing Tai Chi stone and a fabric thereof. Background Art
[0002] Taiji stone is a natural ore, which contains a variety of trace metal mineral elements, has the function of radiating far infrared rays, can promote human blood microcirculation, accelerate metabolism and other health care effects, so that Taiji stone has broad application prospects in fiber fabrics and other aspects. Patent CN103726125B discloses a mite-proof antibacterial polyester staple fiber and its preparation method, which uses Taiji stone, boric acid, clay and other raw materials to make micron-level heat storage anti-mite ceramic powder, and then mixes with silver-loaded nano-titanium dioxide composite antibacterial powder and polyester slices for spinning, and the obtained polyester staple fiber has good antibacterial properties. However, the patent does not improve the hydrophilic hygroscopicity of polyester fibers and fabrics, and compared with inorganic degradable such as silver and nano-titanium dioxide, organic antibacterial agents have good compatibility with material matrices and have little effect on the mechanical properties of materials. Among them, quaternary ammonium salt antibacterial agents have the advantages of fast sterilization speed, strong sterilization ability, good antibacterial broad spectrum, etc., and are widely used in fibers, plastics and other aspects. The present invention aims to use quaternary ammonium salt antibacterial agent to graft-modify polyethylene terephthalate, and then melt-granulate it with Taiji stone micropowder to improve the antibacterial property and hydrophilic hygroscopic property of polyester fiber and fabric. Summary of the invention
[0003] The invention solves the problem that the antibacterial property and the hydrophilic and hygroscopic property of polyester fibers and fabrics are poor.
[0004] The technical solution of the present invention is: a method for preparing composite fibers containing Tai Chi stone, comprising:
[0005] (1) Polyethylene terephthalate is pressed into a film, added to an acetone solution containing benzophenone, stirred and evaporated to remove the solvent, then the polyethylene terephthalate film is added to an aqueous solution containing an alkenyl dicarboxyl quaternary ammonium salt monomer, nitrogen is introduced, and the film is placed under ultraviolet light for grafting reaction, and washed with water, ethanol, and xylene in sequence, and dried to obtain carboxyl quaternary ammonium salt modified PET.
[0006] (2) The Tai Chi stone is ball-milled and sieved to obtain Tai Chi stone powder; the Tai Chi stone powder and carboxyl quaternary ammonium salt modified PET are then added to a high-speed mixer for mixing, and then melt-blended and granulated by a twin-screw extruder to obtain modified PET-Tai Chi stone masterbatch.
[0007] (3) Adding polyethylene terephthalate and modified PET-Taiji stone masterbatch into a screw melt spinning machine for spinning, and then drawing by a drawing machine to obtain a composite fiber containing Taiji stone.
[0008] Preferably, in (1), the mass concentration of benzophenone in the acetone solution is (0.12-0.9) g / L.
[0009] Preferably, in (1), the mass concentration of the aqueous solution of the alkenyl dicarboxyl quaternary ammonium salt monomer is (10-70) g / L.
[0010] Preferably, in (1), the power of the UV lamp is 600-1000 W, and the grafting reaction time is 30-90 min.
[0011] Preferably, in (2), the mass ratio of Taiji stone powder to carboxyl quaternary ammonium salt modified PET is 8-15%.
[0012] Preferably, in (2), the temperature of zones 1 to 6 of the twin-screw extruder is 180-280° C., and the screw speed is 50-100 r / min.
[0013] Preferably, in (3), the mass ratio of polyethylene terephthalate to modified PET-Taiji stone masterbatch is 100:(5-20).
[0014] Preferably, in (3), the temperature of zones 1 to 4 of the screw melt spinning machine is 275-300°C, the spinning rate is 1500-2000 m / min; the drawing speed is 500-800 m / min, and the drawing ratio is 2-3.
[0015] Preferably, the preparation method of the alkenyl dicarboxyl quaternary ammonium salt monomer comprises:
[0016] (1) Add 1,3-dichloro-2-propanol (CAS registration number 96-23-1) and isocyanoethyl methacrylate (CAS registration number 30674-80-7) in a molar ratio of 1:(0.9-1.2) to tetrahydrofuran, heat to 60-65° C., condense and reflux for 6-10 hours, distill under reduced pressure, and dry to obtain an intermediate.
[0017] (2) Add the intermediate, 1-methyl-1H-imidazole-5-carboxylic acid (CAS registration number 41806-40-0) in a molar ratio of 1:(1.8-2.4) to ethanol, heat to 75-80°C, condense and reflux for 36-48 hours, distill under reduced pressure, wash with acetone, and recrystallize the product in ethanol to obtain an olefin dicarboxyl quaternary ammonium salt monomer. The reaction formula is as follows:
[0018]
[0019] Preferably, the antibacterial and moisture-absorbing Tesla double-sided fabric is made of composite fibers containing Tai Chi stones.
[0020] The technical effect of the invention is as follows: the invention uses 1,3-dichloro-2-propanol, isocyanoethyl methacrylate and 1-methyl-1H-imidazole-5-carboxylic acid as reactants to prepare an olefin dicarboxyl quaternary ammonium salt monomer containing two quaternary ammonium salt antibacterial groups and two hydrophilic carboxyl groups, and then ultraviolet light irradiation grafting is performed on polyethylene terephthalate to obtain carboxyl quaternary ammonium salt modified PET, thereby introducing a large number of quaternary ammonium salt antibacterial groups, as well as carboxyl and carbamate hydrophilic groups on the surface of PET.
[0021] The present invention melt-blends and granulates carboxyl quaternary ammonium salt-modified PET and Taiji stone to obtain modified PET-Taiji stone masterbatch, and then melt-blends and spins with polyethylene terephthalate to obtain Taiji stone-containing composite fibers. The composite fibers contain a large amount of quaternary ammonium salt antibacterial groups, which significantly improves the antibacterial properties of the fibers. At the same time, the composite fibers contain carboxyl and carbamate hydrophilic groups, which are beneficial to improving the hydrophilicity of the fiber fabric and showing a higher moisture absorption rate.
[0022] The PET-Taiji stone masterbatch of the present invention has the function of radiating far infrared rays, and can promote blood microcirculation and accelerate metabolism in the human body. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] (1) Add 40 mmol of 1,3-dichloro-2-propanol and 48 mmol of isocyanoethyl methacrylate to 60 mL of tetrahydrofuran, heat to 65°C, condense and reflux for 6 hours, distill under reduced pressure, and dry to obtain an intermediate.
[0026] (2) Add 30 mmol of the intermediate and 54 mmol of 1-methyl-1H-imidazole-5-carboxylic acid to 30 mL of ethanol, heat to 80° C., condense and reflux for 36 hours, distill under reduced pressure, wash with acetone, and recrystallize the product in ethanol to obtain an olefin dicarboxyl quaternary ammonium salt monomer.
[0027] (3) Polyethylene terephthalate is pressed into a film, added to an acetone solution of benzophenone with a mass concentration of 0.37 g / L, stirred and evaporated to remove the solvent, and then the polyethylene terephthalate film is added to an aqueous solution of alkenyl dicarboxyl quaternary ammonium salt monomer with a mass concentration of 30 g / L, nitrogen is introduced, and the film is placed under a 600 W ultraviolet lamp for 90 minutes of grafting reaction, and washed with water, ethanol, and xylene in turn, and dried to obtain carboxyl quaternary ammonium salt modified PET.
[0028] (4) The Tai Chi stone is ball-milled and sieved to obtain Tai Chi stone powder with an average particle size of 3 μm; then 6.5 g of Tai Chi stone powder and 50 g of carboxyl quaternary ammonium salt modified PET are added to a high-speed mixer for mixing, and then melt-blended through a twin-screw extruder. The temperatures of zones 1 to 6 are 180°C, 210°C, 265°C, 280°C, 280°C, and 275°C, and the screw speed is 100 r / min. Granulation is performed to obtain modified PET-Tai Chi stone masterbatch.
[0029] (5) Add 100 g of polyethylene terephthalate and 5 g of modified PET-Tai Chi stone masterbatch into a screw melt spinning machine for spinning. The temperatures of zones 1 to 4 are 275°C, 290°C, 300°C, and 295°C, and the spinning rate is 1800 m / min. The fiber is stretched by a stretching machine at a speed of 800 m / min and a stretching ratio of 3 to obtain a composite fiber containing Tai Chi stone.
[0030] Example 2
[0031] (1) Add 40 mmol of 1,3-dichloro-2-propanol and 36 mmol of isocyanoethyl methacrylate to 80 mL of tetrahydrofuran, heat to 60°C, condense and reflux for 10 h, distill under reduced pressure, and dry to obtain an intermediate.
[0032] (2) Add 30 mmol of the intermediate and 72 mmol of 1-methyl-1H-imidazole-5-carboxylic acid to 25 mL of ethanol, heat to 75° C., condense and reflux for 48 hours, distill under reduced pressure, wash with acetone, and recrystallize the product from ethanol to obtain an olefin dicarboxyl quaternary ammonium salt monomer.
[0033] (3) Polyethylene terephthalate is pressed into a film, added to an acetone solution of benzophenone with a mass concentration of 0.9 g / L, stirred and evaporated to remove the solvent, and then the polyethylene terephthalate film is added to an aqueous solution of alkenyl dicarboxyl quaternary ammonium salt monomer with a mass concentration of 70 g / L, nitrogen is introduced, and the film is placed under an 800 W ultraviolet lamp for 90 minutes of grafting reaction, and washed with water, ethanol, and xylene in turn, and dried to obtain carboxyl quaternary ammonium salt modified PET.
[0034] (4) The Tai Chi stone is ball-milled and sieved to obtain Tai Chi stone powder with an average particle size of 3 μm; then 4 g of Tai Chi stone powder and 50 g of carboxyl quaternary ammonium salt modified PET are added to a high-speed mixer for mixing, and then melt-blended through a twin-screw extruder. The temperatures of zones 1 to 6 are 180°C, 210°C, 265°C, 280°C, 280°C, and 275°C, and the screw speed is 100 r / min. Granulation is performed to obtain modified PET-Tai Chi stone masterbatch.
[0035] (5) Add 100g of polyethylene terephthalate and 10g of modified PET-Tai Chi stone masterbatch into a screw melt spinning machine for spinning. The temperatures of zones 1 to 4 are 275°C, 290°C, 300°C, and 295°C, and the spinning rate is 1500m / min. The fiber is stretched by a stretching machine at a speed of 500m / min and a stretching ratio of 3 to obtain a composite fiber containing Tai Chi stone.
[0036] Example 3
[0037] (1) Prepare an olefin dicarboxyl quaternary ammonium salt monomer according to the method of Example 1.
[0038] (2) Polyethylene terephthalate is pressed into a film, added to an acetone solution of benzophenone with a mass concentration of 0.12 g / L, stirred and evaporated to remove the solvent, and then the polyethylene terephthalate film is added to an aqueous solution of alkenyl dicarboxyl quaternary ammonium salt monomer with a mass concentration of 10 g / L, nitrogen is introduced, and the film is placed under a 600 W ultraviolet lamp for irradiation for 30 minutes for grafting reaction, and washed with water, ethanol, and xylene in turn, and dried to obtain carboxyl quaternary ammonium salt modified PET.
[0039] (3) The Tai Chi stone is ball-milled and sieved to obtain Tai Chi stone powder with an average particle size of 3 μm; then 7.5 g of Tai Chi stone powder and 50 g of carboxyl quaternary ammonium salt modified PET are added to a high-speed mixer for mixing, and then melt-blended through a twin-screw extruder. The temperatures of zones 1 to 6 are 180°C, 210°C, 265°C, 280°C, 280°C, and 275°C, and the screw speed is 80 r / min. Granulation is performed to obtain modified PET-Tai Chi stone masterbatch.
[0040] (4) Add 100 g of polyethylene terephthalate and 15 g of modified PET-Tai Chi stone masterbatch into a screw melt spinning machine for spinning. The temperatures of zones 1 to 4 are 275°C, 290°C, 300°C, and 295°C, and the spinning rate is 1500 m / min. The fiber is stretched by a stretching machine at a speed of 600 m / min and a stretching ratio of 2 to obtain a composite fiber containing Tai Chi stone.
[0041] Example 4
[0042] (1) Prepare an olefin dicarboxyl quaternary ammonium salt monomer according to the method of Example 1.
[0043] (2) Polyethylene terephthalate is pressed into a film, added to an acetone solution of benzophenone with a mass concentration of 0.66 g / L, stirred and evaporated to remove the solvent, and then the polyethylene terephthalate film is added to an aqueous solution of alkenyl dicarboxyl quaternary ammonium salt monomer with a mass concentration of 50 g / L, nitrogen is introduced, and placed under a 1000 W ultraviolet lamp for irradiation to carry out a grafting reaction for 60 minutes, and washed with water, ethanol, and xylene in turn, and dried to obtain carboxyl quaternary ammonium salt modified PET.
[0044] (3) The Tai Chi stone is ball-milled and sieved to obtain Tai Chi stone powder with an average particle size of 3 μm; then 5.2 g of Tai Chi stone powder and 50 g of carboxyl quaternary ammonium salt modified PET are added to a high-speed mixer for mixing, and then melt-blended through a twin-screw extruder. The temperatures of zones 1 to 6 are 180°C, 210°C, 265°C, 280°C, 280°C, and 275°C, and the screw speed is 50 r / min. Granulation is performed to obtain modified PET-Tai Chi stone masterbatch.
[0045] (4) Add 100 g of polyethylene terephthalate and 20 g of modified PET-Tai Chi stone masterbatch into a screw melt spinning machine for spinning. The temperatures of zones 1 to 4 are 275°C, 290°C, 300°C, and 295°C, and the spinning rate is 2000 m / min. The fiber is stretched by a stretching machine at a speed of 800 m / min and a stretching ratio of 2.6 to obtain a composite fiber containing Tai Chi stone.
[0046] Comparative Example 1
[0047] (1) Add 100 g of polyethylene terephthalate into a screw melt spinning machine for spinning, with the temperatures of zones 1 to 4 being 275° C., 290° C., 300° C., and 295° C., and the spinning rate being 1800 m / min; and stretching by a drafting machine at a speed of 800 m / min and a draft ratio of 3, to obtain polyester fiber.
[0048] Comparative Example 2
[0049] (1) The Tai Chi stone is ball-milled and sieved to obtain Tai Chi stone powder with an average particle size of 3 μm; then 6.5 g of Tai Chi stone powder and 50 g of polyethylene terephthalate are added to a high-speed mixer for mixing, and then melt-blended through a twin-screw extruder. The temperatures of zones 1 to 6 are 180°C, 210°C, 265°C, 280°C, 280°C, and 275°C. The screw speed is 100 r / min, and granulation is performed to obtain PET-Tai Chi stone masterbatch.
[0050] (2) Add 100 g of polyethylene terephthalate and 5 g of PET-Tai Chi stone masterbatch into a screw melt spinning machine for spinning. The temperatures of zones 1 to 4 are 275°C, 290°C, 300°C, and 295°C, and the spinning rate is 1800 m / min. The fiber is stretched by a stretching machine at a speed of 800 m / min and a stretching ratio of 3 to obtain a composite fiber containing Tai Chi stone.
[0051] Comparative Example 3
[0052] (1) Add 40 mmol of 3-chloro-1-propanol and 48 mmol of isocyanoethyl methacrylate to 60 mL of tetrahydrofuran, heat to 65°C, condense and reflux for 4 h, distill under reduced pressure, and dry to obtain intermediate 1.
[0053] (2) Add 30 mmol of the intermediate and 30 mmol of 1-methyl-1H-imidazole-5-carboxylic acid to 30 mL of ethanol, heat to 80°C, condense and reflux for 24 hours, distill under reduced pressure, wash with petroleum ether, and recrystallize the product in ethanol to obtain an olefin carboxyl quaternary ammonium salt monomer. The reaction formula is:
[0054]
[0055] (3) Polyethylene terephthalate is pressed into a film, added to an acetone solution of benzophenone with a mass concentration of 0.37 g / L, stirred and evaporated to remove the solvent, and then the polyethylene terephthalate film is added to an aqueous solution of alkenyl carboxyl quaternary ammonium salt monomer with a mass concentration of 30 g / L, nitrogen is introduced, and the film is placed under a 600 W ultraviolet lamp for 90 minutes of grafting reaction, and washed with water, ethanol, and xylene in turn, and dried to obtain carboxyl quaternary ammonium salt modified PET.
[0056] (4) The Tai Chi stone is ball-milled and sieved to obtain Tai Chi stone powder with an average particle size of 3 μm; then 6.5 g of Tai Chi stone powder and 50 g of carboxyl quaternary ammonium salt modified PET are added to a high-speed mixer for mixing, and then melt-blended through a twin-screw extruder. The temperatures of zones 1 to 6 are 180°C, 210°C, 265°C, 280°C, 280°C, and 275°C, and the screw speed is 100 r / min. Granulation is performed to obtain modified PET-Tai Chi stone masterbatch.
[0057] (5) Add 100 g of polyethylene terephthalate and 5 g of modified PET-Tai Chi stone masterbatch into a screw melt spinning machine for spinning. The temperatures of zones 1 to 4 are 275°C, 290°C, 300°C, and 295°C, and the spinning rate is 1800 m / min. The fiber is stretched by a stretching machine at a speed of 800 m / min and a stretching ratio of 3 to obtain a composite fiber containing Tai Chi stone.
[0058] The fiber was sterilized by ultraviolet light; Escherichia coli or Streptococcus aureus was used as the test bacteria. 5 mL of 10 7 CFU / mL of the test bacterial suspension was added to the shaking bottle, and the blank control fiber and the test antibacterial fiber were added respectively. The suspension was shaken at 25°C for 0.5-2h, and then 0.5mL of the shaken bacterial suspension was transferred to PBS buffer and diluted 10 times. 0.5mL of the concentration was 10 6 The diluted bacterial culture solution with CFU / mL was coated on the surface of the agar medium and cultured in a constant temperature and humidity incubator at 37°C for 48 hours. The bacterial count was determined after culture and the antibacterial rate W was calculated.
[0059] W = (BC) / B × 100%. B is the bacterial count of the blank control sample, and C is the bacterial count of the test antibacterial fiber. The polyester fiber of comparative example 1 is used as the blank control fiber. The composite fibers of Examples 1-4 and Comparative Examples 2-3 are used as the test antibacterial fibers. The test results are shown in Tables 1-2.
[0060] Table 1 Escherichia coli inhibition rate
[0061]
[0062]
[0063] Table 2 Antibacterial rate of Staphylococcus aureus
[0064]
[0065] The fibers were woven into fabrics, and the moisture regain of the fabrics was tested according to the method of GB / T 9995-1997. The test results are shown in Table 3.
[0066] Table 3 Moisture regain of fiber fabrics
[0067] Moisture regain (%) Example 1 0.672 Example 2 0.953 Example 3 1.206 Example 4 1.355 Comparative Example 1 0.426 Comparative Example 2 0.419 Comparative Example 3 0.553
[0068] After testing, compared with Comparative Example 1, modified PET-Taiji Stone masterbatch was added to the polyester composite fibers of Examples 1-4. After the modified PET was grafted with olefinic dicarboxyl quaternary ammonium salt monomers, a large number of diquaternary ammonium salt antibacterial groups, as well as hydrophilic carboxyl groups and carbamate groups were introduced on the surface. After melt-blending and spinning, the antibacterial properties and hydrophilicity of the polyester fibers and their fabrics were significantly improved, showing higher antibacterial rate and moisture absorption rate.
[0069] The PET in the PET-Taiji Stone masterbatch of Comparative Example 2 does not contain diquaternary ammonium salt antibacterial groups and hydrophilic carboxyl groups. The antibacterial properties and hydrophilicity of the polyester fiber and its fabric are poor, and the antibacterial rate and moisture absorption rate are low.
[0070] In Comparative Example 3, 3-chloro-1-propanol, isocyanoethyl methacrylate, and 1-methyl-1H-imidazole-5-carboxylic acid are used as reactants to prepare an alkenyl carboxyl quaternary ammonium salt monomer, and then polyethylene terephthalate is grafted and modified to introduce quaternary ammonium salt antibacterial groups and hydrophilic carboxyl groups on the surface of PET to obtain a modified PET-Taiji stone masterbatch. After melt blending and spinning, the antibacterial properties and hydrophilicity of the polyester fiber and its fabric are also significantly improved, but the antibacterial rate and moisture absorption rate are lower than those in the embodiments, mainly because the alkenyl carboxyl quaternary ammonium salt monomer in Comparative Example 3 contains only one quaternary ammonium salt group and one carboxyl group, and its antibacterial properties and hydrophilicity are lower than those of the alkenyl dicarboxyl quaternary ammonium salt monomer containing two quaternary ammonium salt groups and two carboxyl groups in the embodiments.
[0071] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a composite fiber containing Tai Chi stone, characterized in that: The preparation method comprises: (1) Pressing polyethylene terephthalate into a film, adding it to an acetone solution containing benzophenone, stirring and volatilizing the solvent, then adding the polyethylene terephthalate film to an aqueous solution containing an alkenyl dicarboxyl quaternary ammonium salt monomer, passing nitrogen, placing it under ultraviolet light for grafting reaction, washing it with water, ethanol, and xylene in sequence, and drying it to obtain a carboxyl quaternary ammonium salt modified PET; The chemical structural formula of the alkenyl dicarboxyl quaternary ammonium salt monomer is as follows: (2) ball-milling the Taiji stone and sieving it to obtain Taiji stone powder; then adding the Taiji stone powder and carboxyl quaternary ammonium salt modified PET into a high-speed mixer for mixing, and then melt-blending and granulating them through a twin-screw extruder to obtain modified PET-Taiji stone masterbatch; (3) Adding polyethylene terephthalate and modified PET-Taiji stone masterbatch into a screw melt spinning machine for spinning, and then drawing by a drawing machine to obtain a composite fiber containing Taiji stone.
2. The method for preparing composite fibers containing Tai Chi stone according to claim 1, characterized in that: In the above (1), the mass concentration of benzophenone in the acetone solution is (0.12-0.9) g / L.
3. The method for preparing composite fibers containing Tai Chi stone according to claim 1, characterized in that: In the above (1), the mass concentration of the aqueous solution of the alkenyl dicarboxyl quaternary ammonium salt monomer is (10-70) g / L.
4. The method for preparing composite fibers containing Tai Chi stone according to claim 1, characterized in that: In the above (1), the power of the UV lamp is 600-1000W, and the grafting reaction time is 30-90min.
5. The method for preparing composite fibers containing Tai Chi stone according to claim 1, characterized in that: In the above (2), the mass ratio of Taiji stone powder to carboxyl quaternary ammonium salt modified PET is 8-15%.
6. The method for preparing composite fibers containing Tai Chi stone according to claim 1, characterized in that: In the above (2), the temperature of zones 1 to 6 of the twin-screw extruder is 180-280° C., and the screw speed is 50-100 r / min.
7. The method for preparing composite fibers containing Tai Chi stone according to claim 1, characterized in that: In the above (3), the mass ratio of polyethylene terephthalate to modified PET-Taiji stone masterbatch is 100:(5-20).
8. The method for preparing composite fibers containing Tai Chi stone according to claim 1, characterized in that: In the above (3), the temperature of the first to fourth zones of the screw melt spinning machine is 275-300°C, the spinning rate is 1500-2000m / min; the drawing speed is 500-800m / min, and the drawing ratio is 2-3.
9. The method for preparing composite fibers containing Tai Chi stone according to claim 2, characterized in that: The preparation method of the alkenyl dicarboxyl quaternary ammonium salt monomer comprises: (1) Add 1,3-dichloro-2-propanol and isocyanoethyl methacrylate in a molar ratio of 1:(0.9-1.2) to tetrahydrofuran, heat to 60-65° C., condense and reflux for 6-10 hours, distill under reduced pressure, and dry to obtain an intermediate; (2) Add the intermediate and 1-methyl-1H-imidazole-5-carboxylic acid in a molar ratio of 1:(1.8-2.4) to ethanol, heat to 75-80° C., condense and reflux for 36-48 hours, distill under reduced pressure, wash, and recrystallize to obtain an olefin dicarboxyl quaternary ammonium salt monomer.
10. An antibacterial and moisture-absorbing fabric made of composite fibers containing Tai Chi stone obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
An anti-mite and antibacterial polyester staple fiber and its preparation method
CN103726125B
Manufacturing method of Tai chi stone and polyester fiber composite material
CN109355729A
Preparation method of quaternized nanoTaichi stone, quaternized nanoTaichi stone and modified polyester fibers
CN109537089A
Preparation method of quaternary ammonium salt modified polyester resin for antibacterial powder coating
CN112646159A
Antibacterial treatment method for polyester fabric based on surface activation modification
CN115522380A